The Socioeconomic Impact of Surgical Site Infections - Piednoir, Emmanuel; Robert-Yap, Joan; Baillet, Patrice; Lermite, Emilie; Christou, Niki (Frontiers in Public Health, 2021)
Objectives the aim of this brief report is to highlight the economic burden of surgical site infections (SSIs) Methods a narrative review focusing on this subject has been carried out Results SSIs are responsible of important cost. In 2017, a French cohort highlighted a mean cost of each SSI treatment of around 1814 euros; the same year, the Centers for Disease Control and Prevention guidelines evaluated mean cost caused by SSI treatment from 10,443 to 25,546 per SSI. This cost depends on many factors including the patient himself and the type of surgery. Conclusions prevention of the risk of infection is, therefore, a profitable concept for surgery that must be integrated within all the healthcare management worldwide